Comparison of gpd genes and their protein products in basidiomycetes - Sreedhar Kilaru; Ursula Kües (Fungal Genetics Reports, 2005)
We compared promoters, coding sequences, introns and terminators of glyceraldehyde 3-phosphate dehydrogenase genes (gpd) from various basidiomycetes. Coding regions of these housekeeping genes are highly conserved (between 60 to 99% DNA identity) whilst non-coding regions have DNA identities of around 40%. Amongst all homobasidiomycete promoters, the TATA region and a CT-rich region with the potential transcription start sites are highest conserved. Surprisingly, there are no other conserved motifs common to all promoters. Up to five introns are clustered at the far 5´ ends of the genes, hinting to a potential function in efficient gene expression.